2020
DOI: 10.1002/tafs.10246
|View full text |Cite
|
Sign up to set email alerts
|

Hook Avoidance Induced by Private and Social Learning in Common Carp

Abstract: It is essential for fish to respond appropriately when faced with a threatening situation. Accordingly, fish are able to reduce predation risk through learning. In addition to privately learned experiences, fish can acquire social information about a threat by observing the response of conspecifics and use such public information to adapt future behavior through learning. It is unclear if social learning can also influence the behavioral response of fish when faced with human-induced threats in the form of ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 77 publications
(150 reference statements)
0
7
0
Order By: Relevance
“…2018; Lovén Wallerius et al. 2020). Therefore, the low overall capture rate may have occurred due to learning as Muskellunge developed a negative association with lures or the presence of anglers at the ponds.…”
Section: Discussionmentioning
confidence: 99%
“…2018; Lovén Wallerius et al. 2020). Therefore, the low overall capture rate may have occurred due to learning as Muskellunge developed a negative association with lures or the presence of anglers at the ponds.…”
Section: Discussionmentioning
confidence: 99%
“…Although knowledge of how multiple captures affect individual fish behaviour and physiology is more limited, evidence suggests that fishes which are captured can often then demonstrate ‘hook avoidance’ behaviours that reduces their subsequent capture vulnerability. For example, Raat (1985) demonstrated that after carp were hooked once, their vulnerability to subsequent capture was decreased, with experiments by Lovén Wallerius et al (2020) indicating that in addition to direct experience of angling capture leading to hook avoidance, carp can also develop these behaviours through social learning alone. Although domesticated strains of carp are bolder and more vulnerable to angling capture than wild strains, the development of hook avoidance behaviours are similar across both strains (Kleforth et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sharks learned to avoid being recaptured during this study. Learned hook avoidance is quite common in fishes (Lovén Wallerius et al 2020 ).…”
Section: Social Cognitionmentioning
confidence: 99%